2016
DOI: 10.1007/s10689-016-9911-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of renal cell carcinoma and hematologic malignancies (predominantly lymphoid) in individuals and in families

Abstract: The relationship between renal cell cancer (RCC) and hematologic malignancy (HM) in the same individual has been reported for more than 20 years, and is noted in SEER database studies. Family histories suggest a familial association as well. This study evaluates the occurrence of renal cell cancer and hematologic malignancies in individual patients and families, and the occurrence of age-of-onset anticipation among generations. Family history data from our familial patient registry, including more than 700 ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…The phenomenon of concurrent RCC and HM has been reported in the literature, with a focus on gender, timing of the diagnosis of RCC and HM, and most common HM (Table 2 )[ 1 - 5 , 8 , 10 , 11 ]. All except one of the studies in Table 2 documented a higher number of men with both conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The phenomenon of concurrent RCC and HM has been reported in the literature, with a focus on gender, timing of the diagnosis of RCC and HM, and most common HM (Table 2 )[ 1 - 5 , 8 , 10 , 11 ]. All except one of the studies in Table 2 documented a higher number of men with both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…NHL was the most common HM in the majority of these studies. In Dutcher and colleagues’ review of 199 cases of RCC and HM in the same patient identified in the literature ( n = 173) and in their registry ( n = 26) between 1991 and 2016, an association between RCC and HM within families was observed, exemplified by 74 patients with RCC who had 95 family members with HM[ 8 ]. These authors suggested a genetic correlation between RCC and B-cell malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations